1999
DOI: 10.1128/jcm.37.1.233-234.1999
|View full text |Cite
|
Sign up to set email alerts
|

Definition of False-Positive Reactions in Screening for Hepatitis C Virus Antibodies

Abstract: The rate of false-positive hepatitis C virus enzyme immunoassay results was determined to be at least 10% among 1,814 reactive serum samples based on (i) negative results in an independent confirmation assay, (ii) negative PCR results, and (iii) no patients developing clinical or biochemical signs of hepatitis during a 1-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
1
11
0
3
Order By: Relevance
“…The various facilities analysed in the study showed a mean false positivity of 2.2%, 2.8% and 11.1% for HBV, HCV and HIV testing respectively when compared with ELISA ( Table 1 ). These rates are in the range of what was obtained in other studies [ 25 , 27 , 28 ]. The mean false negative was 3.0%, 75.0% and 0.0% for HBV, HCV and HIV respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The various facilities analysed in the study showed a mean false positivity of 2.2%, 2.8% and 11.1% for HBV, HCV and HIV testing respectively when compared with ELISA ( Table 1 ). These rates are in the range of what was obtained in other studies [ 25 , 27 , 28 ]. The mean false negative was 3.0%, 75.0% and 0.0% for HBV, HCV and HIV respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, its use is not currently recommended. 1,11,[27][28][29] Simple assays of cellular immunity, such as interferon enzyme-linked immunospot, might be added to the methods for the diagnosis of HCV infections, 30 mainly in cases with low antibody levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, only a RIBA‐positive subject requires HCV RNA testing because of a low possibility of being viremic (Table 3). However, the RIBA test has disadvantages, such as the variable proportion of indeterminate results 27 and the extended time required for its execution. Therefore, its use is not currently recommended 1,11,27‐29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most laboratories report positive results based only on the antibody and do not verify these results with more specific testing 8 . On the other hand, RIBA also has additional disadvantages, such as the variable proportion of indeterminate results due a nonspecific false reactivity, a phenomenon that has been reported in blood donors, 10,11 and the extended time required for its execution. Therefore, its use is not currently recommended 12‐16 …”
mentioning
confidence: 99%